Emphysema- and airway-dominant COPD phenotypes defined by standardised quantitative computed tomography. Issue 1 (26th May 2016) - Subramanian, Deepak R.; Gupta, Sumit; Burggraf, Dorothe; vom Silberberg, Suzan J.; Heimbeck, Irene; Heiss-Neumann, Marion S.; Haeussinger, Karl; Newby, Chris; Hargadon, Beverley; Raj, Vimal; Singh, Dave; Kolsum, Umme; et al.
EvA (Emphysema versus Airway disease) is a multicentre project to study mechanisms and identify biomarkers of emphysema and airway disease in chronic obstructive pulmonary disease (COPD). The objective of this study was to delineate objectively imaging-based emphysema-dominant and airway disease-dominant phenotypes using quantitative computed tomography (QCT) indices, standardised with a novel phantom-based approach. 441 subjects with COPD (Global Initiative for Chronic Obstructive Lung Disease (GOLD) stages 1–3) were assessed in terms of clinical and physiological measurements, laboratory testing and standardised QCT indices of emphysema and airway wall geometry. QCT indices were influenced by scanner non-conformity, but standardisation significantly reduced variability (p<0.001) and led to more robust phenotypes. Four imaging-derived phenotypes were identified, reflecting "emphysema-dominant", "airway disease-dominant", "mixed" disease and "mild" disease. The emphysema-dominant group had significantly higher lung volumes, lower gas transfer coefficient, lower oxygen ( P O2 ) and carbon dioxide ( P CO2 ) tensions, higher haemoglobin and higher blood leukocyte numbers than the airway disease-dominant group. The utility of QCT for phenotyping in the setting of an international multicentre study is improved by standardisation. QCT indices of emphysema and airway disease can delineate within a population of patients with COPD, phenotypic groups that have typical clinical features known to be associated with emphysema-dominant and airway-dominant disease. Standardisation of quantitative CT improves delineation of emphysema and airway phenotypes in a multicentre study http://ow.ly/10zjhV